2020
DOI: 10.1021/acsabm.0c00985
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Surface Roughness Influences Candida albicans Biofilm Formation

Abstract: The microbial contamination of surfaces presents a significant challenge due to the adverse effects associated with biofilm formation, particularly on implantable devices. Here, the attachment and biofilm formation of the opportunistic human pathogen, Candida albicans ATCC 10231, were studied on surfaces with decreasing magnitudes of nanoscale roughness. The nanoscale surface roughness of nonpolished titanium, polished titanium, and glass was characterized according to average surface roughness, skewness, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…In this case, the actin cytoskeleton is required to re-polarize as a recovery response to continue the cell division process [ 46 ]. It is likely that, here, the condensed F-actin filaments and the lack of cortical actin patches of C. albicans cells on pTi may explain the significantly low cell attachment ( Figure S2 ), and the lack of morphological transformations from round shape to pseudohyphae, or elongated hyphae on pTi, as reported in elsewhere [ 27 ].…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…In this case, the actin cytoskeleton is required to re-polarize as a recovery response to continue the cell division process [ 46 ]. It is likely that, here, the condensed F-actin filaments and the lack of cortical actin patches of C. albicans cells on pTi may explain the significantly low cell attachment ( Figure S2 ), and the lack of morphological transformations from round shape to pseudohyphae, or elongated hyphae on pTi, as reported in elsewhere [ 27 ].…”
Section: Resultssupporting
confidence: 61%
“…One group was directly used for experiments as npTi and the other group consisted of polished (pTi) samples. The polishing process was performed as described elsewhere [ 27 ]. The prepared Ti discs were sterilized by sequentially sonicating with MilliQ water (resistivity: 18.2 MΩ cm, 25 °C), 100% and 70% ethanol (EtOH) (Chem-Supply, Gillman, Australia) for 15 min each.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, due to scarce studies conducted by now, there has not been yet reached a consensus regarding the influence of the surface roughness in the development and adherence of C. albicans fungal cells. The results obtained by Le et al [79] in their study regarding "nanoscale surface roughness influences Candida albicans biofilm formation" have evidenced that that surface topography could influence the adherence of C. albicans cells and also, the results suggested that a specific surface architecture could be used to repel C. albicans attachment, therefore preventing the biofilm formation. Their study revealed that surfaces having an average surface roughness S a less than 20 nm, combined with a certain topography, was highly effective at preventing the attachment of C. albicans.…”
Section: Resultsmentioning
confidence: 97%
“…During denitrification, the change trend of COD increased rapidly from 0 to 12 h, decreased gradually from 12 h to 48 h, and gradually stabilized after 48 h. This result can further explain the variation trend of NO 3 − -N removal during denitrification. Carrera [ 22 ] found, through a wastewater denitrification test, that adding a carbon source enables the C/N in water to exceed 7 and reach efficient denitrification. In this test, the average COD/N ratios of the carbon sources in water follow the order PS (10.4) > MT (7.3) > SD (4.9) > PT (3.3) > CK (0.5).…”
Section: Resultsmentioning
confidence: 99%